[Interkantonale Landmaschinenschau - Brugg (1931-1941)] (1932)
Kataloge, Ausstellungs-Führer (1932-1941); Zeitungsausschnitte (1941) [Ausstellung/Fachausstellung/Messe/Fachmesse/Handel/Industrie/Gewerbe/Gewerbeausstellung/Industrieausstellung/Landwirtschaft/Landwirtschaftsausstellung/Maschinenindustrie/Nutzfahrzeugbau/Landwirtschaftliche Maschinen/Landmaschinen/Traktorenbau/Traktoren/Agrartechnik/Agrotechnologie/Agrarproduktion/Landwirtschaftsmesse/Maschinenbau-Messe Schweiz (Aargau/Kanton)]